2023
DOI: 10.1001/jamainternmed.2023.2442
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Patients With Nonfunctional Adrenal Tumors

Abstract: ImportanceIt is unclear if nonfunctional adrenal adenomas (NFAAs) are associated with increased mortality.ObjectiveTo analyze mortality and causes of death in patients with NFAA.Design, Setting, and ParticipantsA national retrospective register-based case-control study was conducted and included 17 726 patients with a diagnosis of adrenal adenoma in Sweden from 2005 to 2019 who were identified and followed up until death or 2020 as well as 124 366 controls without adrenal adenoma. Individuals with diagnoses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…To the Editor We read with interest the retrospective case-control study by Patrova et al, who demonstrated that nonfunctional adrenal adenoma (NFAA) was associated with an increased overall mortality and mortality owing to cardiovascular disease and cancer. With the lack of data on adrenal hormone measurements, the authors speculated that the development of even slightly elevated cortisol may result in increased cardiovascular disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor We read with interest the retrospective case-control study by Patrova et al, who demonstrated that nonfunctional adrenal adenoma (NFAA) was associated with an increased overall mortality and mortality owing to cardiovascular disease and cancer. With the lack of data on adrenal hormone measurements, the authors speculated that the development of even slightly elevated cortisol may result in increased cardiovascular disease.…”
mentioning
confidence: 99%
“…Screening and confirmation of hyperaldosteronism has traditionally been dichotomous and complex with great variability in reported diagnostic criteria and prevalence . The conclusions of the article would have been further enhanced by reporting the number of patients excluded because they had received renin and aldosterone measurements to support the diagnosis of primary aldosteronism syndrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor We read with great interest the article by Patrova et al on the risk of mortality in patients with nonfunctional adrenal tumors. This study addresses a topic of pivotal importance in adrenal disease that has been the subject of intense research interest in recent years.…”
mentioning
confidence: 99%
“…However, in the article by Patrova et al, the use of NFAA can be misleading. In this population-based retrospective cohort study, the exclusion criteria for hormonal activity were based on the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision ( ICD-10 ) classification codes, according to which patients with Cushing syndrome ( ICD-10 code, E24.0), congenital adrenal hyperplasia (E25.0), primary aldosteronism (E26.0), and pheochromocytoma (E27.5) were excluded from the analyses.…”
mentioning
confidence: 99%